Identify Factors Affecting Bid Value Below 80% in the Procurement of Construction Goods or Services - Nurjanah, Nurul; Soekiman, Anton (Newinera Publisher, 2025)
Competition for construction service is more competitive, the ability to win the tenders is an indicator of success in competition. The method of selecting the service provider with the lowest price often leads to different interpretations. It can be seen from the number of bids below 80% which continues to increase. This research aims to identify the value of the factors that influence the supply below 80%, analyze the dominant factors that have the most influence, and determine the respondents' views based on the company's qualifications in determining the factors that influence the occurrence of bids below 80%. The research method uses the Relative Importance Index (RII). The result of this research obtained 24 factors that affect the value of the offer under 80%. From these 24 factors, ten dominant factors were found, such as (1) the type of project; (2) Project duration; (3) Government Regulations; (4) the risk of carrying out the work; (5) Fluctuations in resource prices; (6) availability of qualified staff; (7) Past failures/profits in similar projects; (8) Tender method (open/close); (9) availability of required funds and office overhead; and (10) Document completeness and design quality.